Basic study on the integration of zakat, village fund, and microfinance management to increase the existence of sustainable MSMEs (empirical Study of the Tolitoli Affirmation Region) - Ismail Ismail; Nurhidayah Usman; M. Ilham Jaya Pernama (Jurnal Mantik, 2026)
This study examines the influence of zakat management, village fund management, and microfinance on the sustainable existence of micro, small, and medium enterprises (MSMEs) in the affirmation area of Tolitoli Regency, Indonesia. Previous studies have generally investigated these financing instruments separately, while limited empirical evidence exists regarding their integrated role in strengthening MSME sustainability in disadvantaged regions. This study therefore offers a novel perspective by integrating social finance, public finance, and microfinance within a single analytical framework. Using a quantitative approach, data were collected from 120 MSME owners through structured questionnaires and analyzed using multiple linear regression. Descriptive results indicate that microfinance received the highest assessment from respondents (mean = 39.15), followed by zakat management (mean = 38.83) and village fund management (mean = 36.83), while sustainable MSME existence recorded a mean score of 40.39. The F-test results show that zakat management, village fund management, and microfinance simultaneously have a significant effect on sustainable MSME existence (F = 151.275; p < 0.001). The t-test further indicates that all variables significantly influence MSME sustainability, with zakat management demonstrating the strongest effect (? = ?0.485), followed by microfinance (? = ?0.275) and village fund management (? = ?0.246). The coefficient of determination (Adjusted R² = 0.791) indicates that 79.1% of the variation in sustainable MSME existence can be explained by the model. Although the regression coefficients are negative, these findings suggest the need for further evaluation of program implementation effectiveness, beneficiary targeting, financing suitability, and institutional coordination. The study contributes to the literature by proposing an integrated social–public–microfinance framework as a foundation for strengthening MSME resilience and sustainability in affirmation areas.